2012
DOI: 10.1371/journal.pone.0043183
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Pattern and Its Association with the Prevalence of Obesity and Related Cardiometabolic Risk Factors among Chinese Children

Abstract: BackgroundThe association of dietary pattern with chronic diseases has been investigated widely in western countries. However, information is quite limited among children in China. Our study is aimed to identify the dietary patterns of Chinese children and examine their association with obesity and related cardiometabolic risk factors.MethodsA total of 5267 children were selected using multistage random sampling from 30 primary schools of 5 provincial capital cities in China. Dietary intake was derived from 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
144
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(153 citation statements)
references
References 68 publications
(58 reference statements)
4
144
1
4
Order By: Relevance
“…Previous research among 5267 children in China indicated that the Western dietary pattern with high intake of red meat and other high-energy-dense foods was positively associated with a higher risk of obesity, a higher level of plasma glucose and TAG (29) . Healthy dietary behaviour would promote a healthy lifestyle, so it is necessary for researchers to guide Chinese populations to control their intake of red meat and increase the intake of vegetables, fruit and fish.…”
Section: Discussionmentioning
confidence: 96%
“…Previous research among 5267 children in China indicated that the Western dietary pattern with high intake of red meat and other high-energy-dense foods was positively associated with a higher risk of obesity, a higher level of plasma glucose and TAG (29) . Healthy dietary behaviour would promote a healthy lifestyle, so it is necessary for researchers to guide Chinese populations to control their intake of red meat and increase the intake of vegetables, fruit and fish.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have been performed to explore any association between DPs and influencing factors. BMI, socioeconomic status, gender, eating habits, biochemical indicators and location of residence in urban or rural areas are reported to be associated with DPs among children and adolescents (7)(8)(9) So far, no comprehensive data is available regarding the children's dietary intake in Iran, though, studies indicated that the dietary quality of school children is not promising (10)(11). In Iran, most of the dietary pattern studies were focused on adults and children's food intake was rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of central obesity is increasing, and studies have suggested that sociodemographic and behavioral factors are involved in its genesis, such as more time spent watching television, inappropriate eating habits, lower parental education level, being female, being young (child), and attending a private school [10][11][12][13] . It is important to identify these factors to create more effective interventions to prevent and treat this disease 14 .…”
Section: Introductionmentioning
confidence: 99%